Occurrence and Intensity of Spinal Pain in Motorcyclists Depending on Motorcycle Type - Roksana Wójcik; Bartosz Trybulec (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
Introduction: Motorcycles in Poland become more and more popular also as convenient means of transport, especially in large cities. Factors influencing on driver during riding the motorcycle are assumed to cause spinal pain in motorcyclist. These factors may vary in motorcycles of different construction or purpose. Few information is available about spinal pain connected with riding a motorcycle. The aim of this study was the assessment of occurrence and intensity of spinal pain in motorcyclists depending on motorcycle type. Material and methods: The study group consisted of 2,124 motorcyclists aged 19-79 yrs., using motorcycle with an engine size bigger than 50 ccm and participating in minimum 1 riding season. An original, on-line available questionnaire composed of questions regarding riding a motorcycle and ailments of all parts of the spine was used. The results underwent statistical analysis using the Statistica 10.0. Results: The results showed that 58.4% respondents experienced pain of at least one part of spine during riding the motorcycle. The biggest percentage (51.1%) of persons with spinal pain in general was found out in cross/enduro type users. Neck pain was significantly connected with riding the sport motorcycle (p=0.001). Conclusions: Spinal pain in motorcyclists depends on the motorcycle type.